2020
DOI: 10.11628/ksppe.2020.23.4.485
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Forest Therapy Program on the Self-Esteem and Resilience of Juveniles Under Protective Detention

Abstract: Background and objective: Juvenile crimes tend to intensify and become habitual in South Korea and juvenile delinquencies must be corrected during adolescence. This study aimed to investigate the effects of a forest therapy program on the self-esteem and resilience of juveniles under protective detention. Methods: We designed the forest therapy program titled "A Dreamy Child, One More Forest!" for one night and two days and a total of 122 juveniles under protective detention participated in the program. Self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Quantitative analysis showed that the program significantly improved self-esteem in UMs. These findings are supported by previous findings (third theme in Table 5) that individuals were provided with the opportunity to develop positive energy that enhances self-esteem and helps with social integration [33].…”
Section: Discussionsupporting
confidence: 90%
“…Quantitative analysis showed that the program significantly improved self-esteem in UMs. These findings are supported by previous findings (third theme in Table 5) that individuals were provided with the opportunity to develop positive energy that enhances self-esteem and helps with social integration [33].…”
Section: Discussionsupporting
confidence: 90%
“…In other words, this research showed that the guided forest therapy program increased participants' self-esteem more than daily life activities. This result is consistent with previous research on forest therapy programs for self-esteem (Lim et al, 2014;Lee et al, 2017;Kim et al, 2020). However, the self-guided forest therapy program showed higher self-esteem than daily life, but there was no statistically significant difference.…”
Section: Rosenberg Self-esteem Scale (Rses)supporting
confidence: 91%
“…While there was some overlap between higher-order concepts for which these and other psychological measures were designed and employed, in Table 1 we attempted to classify measures used in the studies into broader psychological categories. As the table indicates, the studies in our sample sought to assess a wide variety of concepts related to psychological health and wellbeing, from commonly used concepts such as moodemotion [76,77] and depression-anxiety-stress [67,78] to less-common concepts such as nature connectedness [79,80], self-esteem [81,82], mindfulness [83,84], and environmental learning [85,86]. While some of the qualitative studies tapped into similar concepts through the use of unstructured and semi-structured techniques, they also uncovered unique outcomes including an understanding of the "lived experience" of forest therapy including activity preferences and favorite places [87], improvements in the "capacitative body" of knowledge, skills, and motor-sensory capabilities [88], and "embodied spirituality" in experiencing the immensity and interconnectedness of nature [89].…”
Section: Outcome Measures Studiedmentioning
confidence: 99%
“…A few of these targeted populations matched with particular health or wellbeing concerns that were the focus of a subset of studies (n = 76). We categorized this smaller set of studies into five areas of concern: mental health issues (n = 28, 36.9%) such as severe stress/exhaustion [105,106] and trauma/PTSD [34,87]; chronic diseases (n = 24, 31.4%) such as hypertension [65,72] and cancer [47,107]; youth issues (n = 10, 13.0%) such as youth who are placed at-risk [82,108] and those with learning difficulties [109,110]; individuals dealing with chronic pain or fatigue (n = 8, 10.4%) [111,112]; and those dealing with addictions (n = 4, 5.2%) [113,114].…”
Section: Human Characteristics Studiedmentioning
confidence: 99%
See 1 more Smart Citation